2016
DOI: 10.1007/s11192-016-2185-x
|View full text |Cite
|
Sign up to set email alerts
|

Microsoft Academic: is the phoenix getting wings?

Abstract: In this article, we compare publication and citation coverage of the new Microsoft Academic with all other major sources for bibliometric data: Google Scholar, Scopus, and the Web of Science, using a sample of 145 academics in five broad disciplinary areas: Life Sciences, Sciences, Engineering, Social Sciences, and Humanities. When using the more conservative linked citation counts for Microsoft Academic, this data-source provides higher citation counts than both Scopus and the Web of Science for Engineering, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
67
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 8 publications
3
67
0
1
Order By: Relevance
“…The research design was to gather a large recent set of journal articles and to assess the field normalised citation impact advantage of international collaboration overall, when excluding international collaboration, and within broad fields. Scopus was chosen for the data source since it has better coverage of non-English sources than the Web of Science ) and at the time of writing seemed to have more reliable subject classifications than Microsoft Academic (Harzing & Alakangas, 2017) and Dimensions (Thelwall, 2018), with Google Scholar not offering subjectwide classifications (Martín-Martín, Orduna-Malea, Thelwall, & López-Cózar, 2018) and not usually permitting large scale downloading (Harzing, 1997). The data was collected in November 2018 as part of a generic dataset used for multiple studies.…”
Section: Methodsmentioning
confidence: 99%
“…The research design was to gather a large recent set of journal articles and to assess the field normalised citation impact advantage of international collaboration overall, when excluding international collaboration, and within broad fields. Scopus was chosen for the data source since it has better coverage of non-English sources than the Web of Science ) and at the time of writing seemed to have more reliable subject classifications than Microsoft Academic (Harzing & Alakangas, 2017) and Dimensions (Thelwall, 2018), with Google Scholar not offering subjectwide classifications (Martín-Martín, Orduna-Malea, Thelwall, & López-Cózar, 2018) and not usually permitting large scale downloading (Harzing, 1997). The data was collected in November 2018 as part of a generic dataset used for multiple studies.…”
Section: Methodsmentioning
confidence: 99%
“…There are significant positive Spearman correlations between the Microsoft Academic and BKCI citation counts in all fields and years at the p=0.01 level except for Philosophy, Ethics and Religion, and Other Social Sciences in 2016 ( Figures 6-9). The correlations for science fields such as Physics and Mathematics (ranging from .482 to .726 for 2016 and 2013 respectively), Chemical Sciences (.447 to .661), Engineering and Technology (.439 to .643), Computer Science (.376 to 635) and Biological Sciences (.440 to .585) are higher than for the other fields, perhaps because in these fields journal and conference citations are more common and both databases have similar coverage of core science and medicine journals (Harzing & Alakangas, 2017a). As mentioned above, in the sciences most BKCI citations are from articles indexed by WoS databases (92%) rather than books indexed by BKCI (about 5%) (Kousha, & Thelwall, 2015).…”
Section: Rq3: Correlations Between Microsoft Academic and Bkci Or Goomentioning
confidence: 99%
“…and Thelwall (2018), using samples of publications, showed there was uniformity between citation analyses done via MSA and Scopus. Harzing & Alakangas (2017a) also showed, for individual researchers, that the citation counts by MSA were similar to or higher than Scopus and WoS, varying across disciplines.…”
mentioning
confidence: 85%
“…WoS, Scopus and MSA all record and maintain their own citation data. While some research have shown that the citation counts across these sources showed high correlations at the author level and journal level (Harzing, 2016;Harzing & Alakangas, 2017a;Harzing & Alakangas, 2017b), the corresponding effects on a set of universities remain relatively unknown. These analyses were also performed using internal citation counts of each source.…”
Section: Citation Countsmentioning
confidence: 99%
See 1 more Smart Citation